2021
DOI: 10.1002/lt.25973
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplant Recipient, Caregiver, and Provider Perceptions of Cardiovascular Disease and Related Risk Factors After Transplant

Abstract: Liver transplant recipients (LTRs) are at high risk for cardiovascular disease (CVD). We sought to characterize LTR, informal caregiver, and health care provider perceptions about CVD care after liver transplantation (LT) to inform the design of solutions to improve care. Participants included adult LTRs, their caregivers, and multispecialty health care providers recruited from an urban tertiary care network who participated in 90-minute focus groups and completed a brief survey. Focus group transcripts were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Although several barriers in the application of better CV care to LT recipients have been identified, [ 14 ] efforts to overcome these barriers are also being made. Among these, the Northwestern Method © is a mixed‐methods approach that consists in adaptation of practice guidelines by a multidisciplinary panel of experts, identification of barriers for guidance adherence, and implementation and dissemination of the guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several barriers in the application of better CV care to LT recipients have been identified, [ 14 ] efforts to overcome these barriers are also being made. Among these, the Northwestern Method © is a mixed‐methods approach that consists in adaptation of practice guidelines by a multidisciplinary panel of experts, identification of barriers for guidance adherence, and implementation and dissemination of the guidance.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Recent studies have identified several barriers to provide better CV care of LT recipients, such as lack of awareness of CV risk (CVR), lack of confidence to provide high-quality CV care to LT recipients, or difficulties in establishing multidisciplinary teams. [14] Considering all this, we designed a multidisciplinary protocol with the aim of improving the identification and control of post-LT metabolic comorbidities. Here, we report our experience with the first 150 patients included in the protocol and compare their clinical risk profiles at baseline and 12 months after LT with those of a cohort of 100 patients who underwent LT before the inception of the protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by our group identified several barriers to providing multidisciplinary CV disease prevention care to LTRs, including (1) lack of awareness of CV disease risk after LT, (2) lack of confidence in an ability to provide proper CV disease care to LTRs, (3) reluctance to provide CVD care without transplant provider review, and (4) complexity of communication with the multidisciplinary LTRs care team about CVD care. 24 These identified barriers provide potential targets for quality improvement initiatives to improve comanagement of prevalent CV disease risk factors, such as CKD, among LTRs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal method and frequency of testing and treatment remain uncertain. Multiple barriers exist to implement primary and secondary prevention of CHD once identified, including lack of confidence of providers and the complexity of post‐LT care 26 . Table 3 summarizes our practice‐based recommendations for prevention and management of CHD in LTRs.…”
Section: Resultsmentioning
confidence: 99%